How a 12-Hour Shift System Affects the Quality of Performance in Law Enforcement: A Critical Review - John Motsamai Modise (Recent Research Advances in Arts and Social Studies Vol. 5, 2024)
The aim of this study is to review existing data sources to identify what we know about the prevalence of 12-hour shifts in nursing and the impact on both staff and administration personnel in the police. Police work is a 24/7 operation and the issue of police scheduling is of utmost importance in achieving appropriate service area coverage at all times on all days. Specifically, this study aims to address the following questions: What is the prevalence of 12-hour shifts in policing? How much internal variation in shift length is there in policing? What impact does shift length have on the quality of policing and staff experience? To simulate a 12-hour shift rotation and measure the difference in performance if any. This study has reviewed three data sources on 12-hour shifts to explore the potential impact of 12- hour. Significant reductions in neurobehavioural performance during shift work and particularly night work have long been recognised. A 2022 survey of SAPS (South African Police Service) members found that 70% of respondents said they were overworked and 60% of respondents said they were underpaid. There are conflicting reports of the effects of 12-hour shifts on performance, alertness, and safety. Furthermore, research suggests that older shift workers have more sleep disruption and maladaptation to shift work. When this is combined with longer hours at work there may be considerable reductions in performance for older compared with younger workers. Henceforth, 12-hour shifts aren’t suitable for everyone or in all circumstances as heavy lifting and other physical labour may make a job unsuitable owing to the risk of ergonomic injuries and exhaustion.